Improving Students’ Vocabulary Mastery Through Bingo Games - Brigitta Septarini Rahmasari (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This research was aimed to improve the vocabulary mastery of students through Bingo Game. This research was an action research study. The place of the research was at SDK Petra Madiun, East Java, Indonesia. The subject of the research was fourth grade students of SDK Petra Madiun, consisting 30 students. It was done in two cycles. The researcher did some steps for each cycle. They were planning, action, observation, and reflection. The data were collected by using test, observation, and interview. Furthermore, the data were analyzed by using descriptive statistics. It was compared between the scores of pre test (before implementing Bingo game) and post test (after implementing Bingo game). The research findings showed that vocabulary mastery of most students improved after Bingo Game was used in the teaching and learning process. It was indicated by the increase of the mean of students’ vocabulary score in the pre-test and post-test (67.22 to 80.57). The students’ involvement and classroom interaction during the implementation of the game improved. It was showed by students’ enthusiasm during the game. They tried to be the first winner and raised their competitiveness among them. In addition, the implementation of Bingo Game and the complementary actions were successful to help the students memorize and understand new words easily. In conclusion, the students’ vocabulary mastery improved through the implementation of Bingo Game.